PENGARUH PERCEIVED INTERACTIVITY, DAN PERCEIVED USEFULNESS TERHADAP BEHAVIORAL INTENTION DENGAN USER SATISFACTION SEBAGAI VARIABEL INTERVENING; APLIKASI GMS CHURCH SURABAYA - Natasha Giovanna Tanugraha (Jurnal Strategi Pemasaran, 2021)
This study aims to analyze the effect of Perceived interactivity and Perceived usefulness on Behavioral intention with User satisfaction as an Intervening Variable in the GMS Church Surabaya Application. The data in this study were collected through an online survey by distributing questionnaires to 150 respondents. The research method used is a quantitative approach using Partial Least Square and SPSS. The results of the study prove that Perceived interactivity is positively related to User satisfaction, Perceived interactivity has a significant effect on Behavioral intention, Perceived usefulness has an effect on User satisfaction, Perceived usefulness has an effect on Behavioral intention, Perceived interactivity and Perceived usefulness have no significant effect on Behavioral intention through User satisfaction as mediation.